PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, KOMPENSASI DAN KEPUASAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Yuda Adiputera, I Made; Suana, I Wayan (E-Jurnal Manajemen, 2015)
Human resources management is a necessity and no longer an option if the company wants to develop. This study aims toideterminetheieffect of transformational leadership style, compensation and job satisfaction partially on organizational citizenship behavior (OCB) at the Hospital Civil Servants Cooperative Kamadhuk Sanglah. 75 respondents were sampled, with a census method. Data collected through questionnaires. The analysis technique used is multiple linear regression analysis. The results showed that, transformational leadership, compensation and job satisfaction have a significant effect on organizational citizenship behavior in KPN Kamadhuk Sanglah Hospital.
Keywords: Transformational Leadership, Compensation, Job Satisfaction, Organizational Citizenship Behavior